Students’ perception of self-efficacy and academic engagement in School of Health of the Polytechnic Institute of Porto: an observational study - Amorim, Manuela (2022)
The intense increase in students in Higher Education, observed in recent decades, has promoted profound changes quantitative and qualitative in demand, frequency, and student profile. In the context of these changes, we conducted a study to evaluate the self-efficacy and academic engagement of students using an online questionnaire. It includes some sociodemographic variables and the Self-Efficacy Scale in Higher Education (AEFS) and University Student Engagement Inventory (USEI). It was possible to verify that students had a score for academic engagement above the average, revealing an overall high level of academic engagement, an indicator of student success. Regarding self-efficacy, the score obtained is above 4 (on a scale of 1 to 5), close to 5, in social interaction, which indicates that these students overall have relatively robust self-efficacy beliefs. In all cases, the low values of standard deviation reveal a good degree of agreement between responses.